Pengaruh Bangunan Hijau, Kepemilikan, Ukuran, dan Leverage terhadap Nilai Perusahaan Melalui Keuntungan dan Kebijakan Pajak Insentif sebagai Moderator pada Perusahaan Sektor Properti yang Terdaftar di Bursa Efek Indonesia - Adistie Prestiani Putri; Tri Ratnawati; Ida Ayu Sri Brahmayanti (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examined the effect of green building certification, ownership structure, firm size, and leverage on firm value through profitability, and evaluated the moderating role of the government-borne value added tax incentive in property sector companies listed on the Indonesia Stock Exchange during 2021–2024. The research used a quantitative causal explanatory design with 38 firms selected by purposive sampling. Secondary data from audited financial, annual, and sustainability reports were analyzed using Structural Equation Modeling with the Partial Least Squares approach and SmartPLS 4.0, with bootstrapping to test significance. The results showed that green building certification, ownership structure, and leverage had a negative and significant effect on profitability, while firm size had a positive and significant effect on profitability. Green building certification and ownership structure did not significantly affect firm value, whereas firm size had a negative and significant effect and leverage and profitability had a positive and significant effect on firm value. Profitability negatively mediated the effects of green building certification, ownership structure, and leverage on firm value and positively mediated the effect of firm size, while the value added tax incentive did not significantly moderate the relationship between profitability and firm value.